Frailty and Intrinsic Capacity: Two Distinct but Related Constructs - Belloni, Giulia; Cesari, Matteo (Frontiers in Medicine, 2019)
Frailty is a clinical condition characterized by the individual’s increased vulnerability to endogenous and exogenous stressors. It is determined by the reduction of homeostatic capacities of the organism and responsible for a marked risk of adverse health outcomes (including functional loss and mortality). Frailty originates from the geriatric background and may pave the way towards a model of care centred on the person, deviating from the traditional and obsolete disease-focused approach. Unfortunately, many controversies have affected the field of frailty over the years and ambiguities have been growing. In particular, the common use of frailty as condition to “exclude” from interventions is a worrisome trend. In fact, the detection of frailty should instead represent the entry point for a more in-depth analysis with the aim of identifying the causes of individual’s increased vulnerability and implementing a person-tailored intervention plan. With the aim of promoting a more comprehensive and appropriate assessment of the aging population, the World Health Organization introduced the concept of intrinsic capacity (IC), defined as the composite of all physical and mental capacities that an individual can draw upon during his/her life. Frailty and IC are two constructs stemming from the same need of overcoming traditional medical paradigms that negatively impact on the correct way clinical and research practice should be conducted in older persons. In this article, we describe the similarities and differences between the two constructs, highlighting how geriatric medicine contributed to their development and will be crucial for their further integration in future healthcare models.